Análisis Financiero a la Distribuidora Imelda de Jaramillo Cía Ltda de la ciudad de Loja, Periodos 2021 – 2022. - Quishpe Quizhpe, Brayan Ricardo (2024)
The Degree Work of Curricular Integration called Financial Analysis of the Distributor Imelda de Jaramillo Limited Company of Loja city. Periods 2021 - 2022 was conducted in order to know, identify and analyze the financial economic situation, in order to issue conclusions and recommendations for the benefit of the growth of the distributor, in addition, to meet a prerequisite to get the degree and title of Bachelor of Accounting and Auditing. Based on the objectives set out, the review of the Financial Statements was carried out, thus performing the vertical analysis, which allowed determining the percentage that make up the accounts in relation to the group and subgroup, where it was determined that within the Assets the accounts with the greatest relevance are Financial Assets with a value of $3,954,955.46 representing 64.77% for the year 2021 and $3,867. 689.83 with a percentage of 66.52% for the year 2022, followed by Inventories with a value of $1,692,925.36 and a percentage of 27.73% for the year 2021 and $1,635,112.65 with a percentage of 28.12% for the year 2022, values that are given by action of the main activity of the distributor, which is the purchase and sale of products classified as basic necessities, these accounts belonging to Current Assets. In turn, in order to know the variations that occurred within the economic structure, the horizontal analysis was applied, where an increase in income was evidenced due to this action, its profit increased by 30.61%, greatly benefiting the profitability of the distributor. Then, the application of financial indicators was carried out in order to determine the level of profitability, liquidity and indebtedness maintained in the analyzed periods, obtaining as a result that the distributor has sufficient liquidity to meet the current obligations it has active, in turn, within the activity indicators for the year 2021 the inventory had a turnover of 10.88 times and for the year 2022 a turnover of 11.67 times, which indicates that the merchandise had more output compared to the previous year. With respect to indebtedness, mainly from its suppliers, from 74.20% in 2021, it was reduced to 70.23% in 2022. After applying the profitability indicators, its net margin for 2021 was 1.34% and for 2022 it was 1.63% in relation to its revenues, values that are low in relation to the high cost of sales, which for the second period increased proportionally in relation to the increase in sales. Finally, a financial report was prepared where the results of the application of the financial analysis and indicators were presented in a summarized and concrete manner, containing conclusions and recommendations to be considered by the General Manager of the 2 distribution company, with the purpose of informing about the economic-financial situation and at the same time allowing him to make the best decisions for the benefit of the entity.